PENGGUNAAN MODEL EXAMPLE NON EXAMPLE BERBANTUAN MEDIA FLASHCARD TERHADAP HASIL BELAJAR IPAS SEKOLAH DASAR - Nurmitasari Nurmitasari; Mazroatul Akhiroh; Sofia Khoirunnisa; Riza Umami; Dwinta Salsabila; Syukri Al Hamid (LPPM Universitas Cipta Mandiri, 2026)
This study aims to determine the effect of the Example Non Example learning model assisted by flashcard media on elementary students’ learning outcomes in Natural and Social Sciences (IPAS). The research was motivated by the low learning outcomes and lack of student engagement in conventional IPAS learning. The study used a quantitative approach with a Posttest-Only Control Group Design. The normality test using the Liliefors method showed that the data were normally distributed, with Lcalculated for the experimental class 0.1524 and control class 0.1411, both lower than Ltable 0.195. The homogeneity test result indicated Fcalculated 1.099 < Ftable 2.25, meaning the data were homogeneous. The two-tailed t-test showed tcalculated 4.15 > ttable 2.02, and the one-tailed t-test showed tcalculated 4.15 > ttable 1.68. These results indicate a significant difference between students taught using the Example Non Example model with flashcard assistance and those taught using the expository model. Therefore, the Example Non Example model assisted by flashcard media effectively improves IPAS learning outcomes among elementary students.